ANALISIS BIBLIOMETRIK TENTANG PBL SEBAGAI MODEL PEMBELAJARAN EFEKTIF UNTUK MENGASAH KEMAMPUAN BERPIKIR KRITIS SISWA: Bibliometric Analysis of PBL as an Effective Learning Model to Enhance Students' Critical Thinking Skills - Amanda, Nadila Permata; Hasanuddin, Hasanuddin (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
The aim of this study is to examine the evolution and research trends related to PBL, which is considered an effective learning model for enhancing students’ CTS, using a bibliometric approach. The method used is a bibliometric analysis of literature sourced from Google Scholar, focusing on publications between 2020 and 2025. VOSviewer was utilized to identify relationships among frequently used terms, authors, sources, and keywords after data was collected using the PoP software. The analysis results indicate that PBL is becoming increasingly popular in schools and has been proven to have a positive impact on the development of students’ CTS. Furthermore, it was found that PBL contributes significantly to CTS development, and topics such as teaching and learning processes PBL, CTS, and the influence of problem-based models are frequently associated keywords in PBL research. The findings of this study are expected to serve as a foundation for further research and provide insights for education practitioners in designing more contextual and efficient learning models.